2023
DOI: 10.1002/agt2.332
|View full text |Cite
|
Sign up to set email alerts
|

Efficient scarless skin regeneration enabled by loading micronized amnion in a bioinspired adhesive wound dressing

Abstract: Complete skin reconstruction is a hierarchical, physiological assembly process involving healing of the epidermis, dermis, vasculature, nerves, and cutaneous appendages. To date, few works have reported complete skin regeneration, particularly lacking vascular structures and hair follicles after full skin defects. In this study, a hydrogel derived from the skin secretion of Andrias davidianus (SSAD) that features adhesiveness was used as a bioactive scaffold to load micronized amnion (MA). The SSAD hydrogel wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
(119 reference statements)
0
6
0
Order By: Relevance
“…[ 1 ] Therefore, wound healing has been the focus of research and attention by many groups and industries. [ 4–7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Therefore, wound healing has been the focus of research and attention by many groups and industries. [ 4–7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Acupuncture has a history of over 3000 years in China. [8] During recent decades, as a potential alternative method for the treatment of diseases, acupuncture has received wide attention across the world [9][10][11][12][13] and nerve stimulation has been emerging as a potential therapeutic regimen to treat systemic inflammation. [14,15] It began with the discovery that electrical stimulation of cervical vagal efferent would suppress systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, our previous study demonstrated that the SSAD was able to promote the scarless healing of skin incisions and full-thickness skin defects [8] by recruiting endogenous stem cells, regulating local microenvironment including promoting the migration and proliferation of keratinocytes (KCs) and activating the mitogenactivated protein kinase (MAPK) signaling pathway, as well as being rich in a variety of growth factors related to wound regeneration, blood vessel formation, and re-epithelialization such as vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), epidermal growth factor (EGF), hepatocyte growth factor (HGF), and basic fibroblast growth factor (bFGF). [9,10] Compared with the GelMA-alone hydrogel microspheres (GMs), those supplemented with SSAD (SSAD@GMs) had rougher surfaces, which increased the adhesion of cells on the microspheres, improved the proliferation of cells, and promoted the cell functions.…”
Section: Introductionmentioning
confidence: 99%
“…[29] Moreover, they can protect wounds from infections, absorb excess exudate, and promote the dissolution and exfoliation of deep necrotic tissue. [29,30] However, hydrogels for controllable release are usually prepared using UV light, heating, or catalysts, which may potentially harm the essential biological components of nanovesicles. [31] Although temperature-sensitive hydrogel PF-127 has been utilized for in situ gelation in esophagus without affecting the functions of nanovesicles, [32] it is not suitable for skin with unstable temperatures.…”
Section: Introductionmentioning
confidence: 99%